2010
DOI: 10.4314/wajm.v28i5.55012
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Vaginal Hysterectomy and its Impact on Residency Training

Abstract: BACKGROUND: The advantages of vaginal hysterectomy over abdominal hysterectomy include lower morbidity, shorter hospital stay, and reduced cost to the patient. It is, therefore, important to pass the required skill for vaginal hysterectomy unto trainees. OBJECTIVE: To determine the proportion of vaginal hysterectomies done in a residency training institution in Nigeria and its possible impact on the proficiency of future gynaecologists in performing the procedure. METHODS: A chart review was done on all docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…The ratio of vaginal hysterectomy to abdominal hysterectomy in the United States is approximately 1:4 [6]. The ratio of vaginal hysterectomy to abdominal hysterectomy in Nigeria ranges from 1:4 [21] to 1:9 [12]. Nigerian figures are lower than what is obtainable in other advanced countries despite vaginal route as gynaecologist's route of choice for hysterectomy for benign gynaecological conditions.…”
Section: Incidencementioning
confidence: 63%
See 3 more Smart Citations
“…The ratio of vaginal hysterectomy to abdominal hysterectomy in the United States is approximately 1:4 [6]. The ratio of vaginal hysterectomy to abdominal hysterectomy in Nigeria ranges from 1:4 [21] to 1:9 [12]. Nigerian figures are lower than what is obtainable in other advanced countries despite vaginal route as gynaecologist's route of choice for hysterectomy for benign gynaecological conditions.…”
Section: Incidencementioning
confidence: 63%
“…Most centres hardly do up to five vaginal hysterectomies in a year. In most centres, residents in training hardly perform vaginal hysterectomy and by the time they finish the programme, no skill is acquired in performing vaginal hysterectomy [11,12]. In advanced countries a resident is expected to perform minimum of 25 vaginal hysterectomies during the residency training programme [31], however, in Nigeria a resident may not have watched or assisted in up to 10 vaginal hysterectomies before the residency programme is completed.…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…If learned properly, it instils confidence in surgeons to undertake this procedure routinely in all technically feasible cases. Ocheke et al [28] also concluded that resident's inadequate exposure and training of vaginal hysterectomy may have potential implications on future proficiency to perform this method of surgery that has documented advantages in the best interest of patients.…”
Section: Resultsmentioning
confidence: 99%